(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2019)
Deep-water benthic foraminifera were reported from lower Tithonian abyssal deposits lying above a barren interval of radiolarites in the Magura Basin (Western Carpathians). The analysis of morphogroups shows that the assemblage is represented by increased globular chambered morphogroups of both agglutinated and calcareous benthic foraminifera and planoconvex calcareous benthic foraminifera. The composition of the benthic foraminiferal assemblage points to a stressed setting particularly occurring in environments with increased organic flux and depleted oxygen in bottom and pore waters, as indicated by the scarcity of strictly epifaunal agglutinated foraminifera and the absence of strictly epifaunal calcareous benthic foraminifera. The assemblage is compared with Oxfordian – Tithonian assemblages reported from deep-water facies and shelf assemblages from the Boreal, Tethys and Atlantic realms.